Environmental Forensics : Contaminant Specific Guide. - Morrison, Robert D. (Elsevier, 2005)
Environmental forensics is the application of scientific techniques for the purpose of identifying the source and age of a contaminant. Over the past several years, this study has been expanding as a course of study in academia, government and commercial markets. The US Environmental Protection Agency (EPA), Federal Bureau of Investigation (FBI), and Federal Emergency Management Agency (FEMA) are among the governmental agencies that utilize the study of environmental forensics to ensure national security and to ensure that companies are complying with standards. Even the International Network.